Pakistan : The Economy of An Elitist State - Ishrat Husain (Karachi, Pakistan Oxford University Press, 1999)
"This analysis into the prevailing economic situation in Pakistan has three distinguishing features. It is an exhaustive, analytical history of economic development in Pakistan during the last fifty years; it provides an explanation of Pakistan's economic performance in the political context, and compares it with other South Asian countries and with East Asia; it outlines for Pakistan an agenda of economic and social reforms based on a model of shared growth to see the country into the twenty-first century." "The main thrust of the book is that the respective roles of the state and the market have been reversed in the case of Pakistan, with the result that the benefits are reaped by the elite classes only."--Jacket.
Include Index, Bibliography and Epilouge
Keywords: Pakistan -- Economic history -- Economic policy